Preliminary Report of Palaeoenvironmental Investigations at under Whitle, Sheen, Staffordshire - Parker Heath, Ian; Davies, Tudur (Medieval Settlement Research, 2023)
Since 2015, a small local heritage group (TFIG: the Tudor Farming Interpretation Group) has been investigating the origins of a farmstead known as Under Whitle near Pilsbury Castle, on the Staffordshire/Derbyshire border in the Peak District, centred on SK107640 (Fig. 1). The archaeological potential of the farmstead was first recognised by Rylatt (2005), who identified several standing earthworks of mixed date within the study area, including a possible building platform, holloways, enclosures, and a field system with lynchet, ditches, banks and areas of ridge-and-furrow likely to date to the medieval period. In addition to these features, there were areas identified as having potential for the preservation of palaeoenvironmental remains.